FAKTOR FAKTOR YANG MEMPENGARUHI MINAT NASABAH MEMILIH PRODUK SIMPANAN SA’ALEANT PADA CU PANCUR KASIH CABANG AMPERA PONTIANAK - B21107007, Reza Nofaldi (Jurnal Pembangunan dan Pemerataan, 2014)
The title of this study is “factors that affect the interest of customers choose savings products sa’aleant at CU Pancur Kasih branch ampera Pontianak’’. The government makes the cooperative as a container and a tool of economic policy in an effort to create conditions of fair and prosperous society for all, ass stated in the article 33 ayat 1 UUD 1945: “the economy is structured as a joint venture based on the principle of kinship’’. The purpose of the study is to analyze the factors that affect the interests of the customer in choosing savings products sa’aleant CU Pancur Kasih Branch Ampera Pontianak. in this study using a descriptive method, descriptive method aims to describe the nature of things in progress in the research carried out and examine the causes of a particular symptom. The results of this study indicate that members CU choosing due to, factors fairly high interest rate in a year. Based on the above results, it can be deduced that the members CU choosing deposits sa’aleant because interest rates and at CU it is easy to make savings and loan.